Reserve support of avionics safety stability of perspective aircrafts - Воробьев, В. М.; Киселев, А. Д.; Рутов, А. М.; Вашку, О. Ж. (Proceedings of National Aviation University (archive), 2000)
Avionics safety stability of perspective aircrafts is the characteristics allowing to considerably broaden their possibilities and to increase functional efficiency